A Study of Rural Market in India and Relevance of Thompson Rural Market Index in the Rural Market in Contemporary India (International Journal of Innovative Research in Engineering & Management, 2023)
Rural market in India has been grown  faster than ever in previous decade. In different parts of  country, the villages have seen transformation. The  government of all the parties in different states had it  clear in their minds that if villages will not grow the  growth of state in not possible. Some credit can be given  to consumerism too. The urban market is becoming  saturated, whereas villagers have plenty of disposable  income thanks to bumper harvests in recent years. Rural  markets are estimated to have three times the potential of  the European market. This clearly defines the amount of  business that can be generated in rural Indian markets.  For quite some time, the allure of rural India has been the  subject of intense debate among corporate executives.  With increased rural literacy and media exposure, people  in rural areas are becoming more conscious of their  purchasing decisions, just like their urban counterparts.  This makes it even more difficult for businesses to  comprehend the rural consumer's purchasing habits,  consumption patterns, and needs and desires. This thesis  follows the path of rural marketing. It goes on to discuss  the challenges that companies face when marketing their  products, as well as the strategies that companies can use to overcome these challenges.
Keywords: Rural Marketing; Rurak Market segmentation; Village market